(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article discusses the features of formation orthoepic skills and abilities of foreign students in the preparatory department, who study Ukrainian language as foreign language. Suggested exercises develop international students’ proper literary pronunciation of linguistic units on different levels.